A contribuição da governança corporativa para a cooperativa de crédito SICOOB integrado - Dalbosco, Silvana (2014)
This search aims at telling which is the contribution of cooperate management to credit unions. The unions are organizations that have difficulties with their management system, once they are driven by several people’s interests. These problems get even harder when it is about credit unions that work with sources and quotas from their own members to offer banking credit and services to themselves, this is the reason why they need a new way of management which is capable of obtaining a good economic performance and an advantage on the market it operates. For this, some of them are using the corporate management attempting to answer to a union targets. Corporate management is a way of strategic management which operates in companies offering them services of controlling and monitoring established by their owners, thus the decisions are made according to the union partners or investors. In a view of the evolution in the number of unions in Brazil, the general objective of this search is identifying the contribution of corporate management in the Cooperativa de Crédito de Livre Admissão do Sudoeste Integrado and purposing to answer the question about the problem focused here. This work wants to answer the following specific objectives: raising which are the possible management actions; knowing, inside the union, which are the actions that could be used; noticing, according to the information previously gathered, which action points are used and which ones are not. Corporate management has a great contribution to Sicoob Integrado, it improved its transparency, promoted investors warranties and the confidence of its members. With this research, applied to Sicoob Integrado, it was possible to have an idea of how the corporate management is contributing to the credit unions bringing them improvement to their image and, consequently, contributing to increase the number of investors, this amplifies credit limits and negotiation opportunities. In general, it is possible to say that the Union is adapted to several actions of corporate management, however it is still necessary to obtain improvement.